A first Czech analysis of 1887 cases with monoclonal gammopathy of undetermined significance - Sandecká, Viera; Hájek, Roman; Pour, Luděk; Špička, Ivan; Ščudla, Vlastimil; Gregora, Evžen; Radocha, Jakub; Walterová, Lenka; Kessler, Petr; Zahradová, Lenka; Adamová, Dagmar; Valentova, Kamila; et al. (European journal of haematology, 2017)
INTRODUCTION: Monoclonal gammopathy of undetermined significance (MGUS) is a premalignant condition with a risk of malignant conversion. PATIENTS AND METHODS: With the aim to estimate the cumulative risk MGUS progression to hematologic malignancies, we analyzed a nationwide population-based cohort of 1887 MGUS patients from the Czech Registry of Monoclonal Gammopathies (RMG) between 2007 and 2013. RESULTS: During the follow-up period (median 4 years; range 0.6-34.8), progression to hematologic malignancies was observed in 8.6% (162 of 1887) of patients. Factors associated with progression were as follows: M-protein concentration ≥1.5 g/dL, pathological sFLC (<0.26 or >1.65) ratio, bone marrow plasma cells (BMPCs) in cytology >5%, immunoparesis, age ≥69 years, and the level of serum hemoglobin at baseline <12.0 g/dL. Combining these factors, we propose a new risk model (CMG model). The risk of progression at 10 years was 1.6%, 16.9%, 22.9%, 39.4%, and 52.3%, respectively, if 0 (reference group), one, two, three, or four to five risk factors are present (P<.001) with HR 63 times higher compared to the reference MGUS group. CONCLUSION: The new CMG model was established with an advantage for better identification of MGUS patients at low risk.
Keywords: risk factors; Registries; surveillance populace; proporcionální rizikové modely; Bone Marrow; Humans; lidé středního věku; Proportional Hazards Models; monoclonal gammopathy; monoklonální gamapatie nejasného významu; Disease Progression; registrace; In Situ Hybridization, Fluorescence; Female; rizikové faktory; Aged; senioři; lidé; plazmatické buňky; Biomarkers; Plasma Cells; nádorová transformace buněk; multiple myeloma; biologické markery; ženské pohlaví; Kaplanův-Meierův odhad; Male; hybridizace in situ fluorescenční; Middle Aged; Monoclonal Gammopathy of Undetermined Significance; kostní dřeň; Czech Republic; progression; Aged, 80 and over; Cell Transformation, Neoplastic; senioři nad 80 let; progrese nemoci; Kaplan-Meier Estimate; Myeloma Proteins; Population Surveillance; Risk Assessment; myelomové proteiny; Česká republika; mužské pohlaví; hodnocení rizik; Risk Factors